2005
DOI: 10.1002/arch.20046
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mode of action and differential activity of new ecdysone agonists against mosquitoes and moths

Abstract: THQ (1-aroyl-4-(arylamino)-1,2,3,4-tetrahydroquinoline) compounds were identified by FMC Corporation in cell-based assays that used ecdysone receptors from Drosophila melanogaster, Heliothis virescens, or Plodia interpunctata. THQ compounds showed weak insecticidal activity against H. virescens and, therefore, were not developed further. Several ecdysone agonists based on THQ chemotype have been synthesized and tested for their activity against a number of EcRs in transactivation assays. The THQ compound, RG-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…83% determined by 1 H NMR analysis), which was used for the next reaction without further purification. [1,3,4]…”
Section: Synthesis Of 2-chlorophenacyl Bromidementioning
confidence: 98%
See 1 more Smart Citation
“…83% determined by 1 H NMR analysis), which was used for the next reaction without further purification. [1,3,4]…”
Section: Synthesis Of 2-chlorophenacyl Bromidementioning
confidence: 98%
“…Among them, tetrahydroquinoline (THQ) [4], N-alkyl-3,5-di-tert-butyl-4-hydroxybenzamide [5], α-acylaminoketone [6], oxadiazoline [7], and γ-methylene-γ-lactam [8] have been described over the past two decades. In 2009, Holmwood and Schindler reported that imidazole (IMD) and imidazothiadiazole (ITD)-type compounds are ecdysone agonists (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…RH-2485 or methoxyfenozide, RH-0345 or halofenozide, and RH-5992 or tebufenozide from Rohm & Haas Co, Spring House, PA; now Dow AgroSciences, Indianapolis, IN; and ANS-118 or chromafenozide from Sankyo Agro Co. Ltd (presently Mitsui Agro Inc., Japan) and Nippon-Kayaku Co. Ltd (both Tokyo, Japan) Sawada et al 2003 ) , are mainly used to control lepidopteran pests although halofenozide formulations also exist against soil-dwelling coleopterans (Dhadialla et al , 2005 . Other non-steroidal analogs include AAKs (which resemble much DAHs; Tice et al 2003a, b ) and THQs (Smith et al 2003 ;Palli et al 2005b ) (Fig. 6.3 ).…”
Section: Chemistry Of Analogsmentioning
confidence: 98%
“…In this study, a library of non-steroidal ecdysone agonists containing different mother structures with diacylhydrazine (DAH) and other related analogues such as a -acylaminoketone (AAK) and tetrahydroquinoline (THQ) (Smith et al 2003 ;Tice et al 2003a, b ;Palli et al 2005b ) (Fig. 6.3 ) was tested for activation of the EcREbased reporter in S2 cells and the activities were compared with activities obtained in lepidopteran Bm5 cells (Wheelock et al 2006 ;Soin et al 2010a, b ) .…”
Section: Differences Among Cell Lines Derived From Insect Species Of mentioning
confidence: 99%
“…However, among them, tetrahydroquinoline-type compounds are effective against Diptera, particularly against mosquitoes. 20) Previously, we found three new compounds with novel mother structures that specifically bind to EcR using in silico screening, 21) but they are inactive under an in vivo assay. Pesticides that have been developed and used recently are required to be less toxic to mammals and labile in environment.…”
Section: Introductionmentioning
confidence: 99%